Assessment of antenatal care satisfaction amongst postpartum women at the University College Hospital, Ibadan, Nigeria - Opeyemi Adeniyi Adedeji; Timothy A.O. Oluwasola; Funmilola Margaret Adedeji (Elsevier, 2023)
Background: Maternal mortality is unacceptably high especially in developing countries. About 287,000 women died during and following pregnancy and childbirth in 2020. The vast majority of these deaths (95 %) occurred in low and lower middle countries in 2020 and most could have been prevented. Every day in 2020, approximately 800 women died from preventable causes related to pregnancy and childbirth. Utilization of antenatal visit has been shown to improve birth outcome as well as the maternal outcome during pregnancy-related events, giving a positive impact when the visit frequency and care are adequate while satisfaction has equally been an important outcome measures of quality of care. In order to improve feto-maternal outcome and turn the tide against maternal deaths, it is expedient to assess the satisfaction of women who had experienced antenatal care with the aim of identifying areas requiring additional attention. Objective: This study aimed to assess the level of antenatal care satisfaction of postpartum women and factors associated with satisfaction at the University College Hospital (UCH), Ibadan and their future intention for subsequent utilization of antenatal care. Methods: A descriptive cross-sectional study of 261 women in the postnatal ward using simple random sampling technique was conducted with an interviewer-administered structured questionnaire. Items in the questionnaire included sociodemographic and obstetric variables, assessment of quality of amenities, waiting time and level of satisfaction. Data was entered, cleaned and analyzed by computer using the Statistical Package for Social Sciences Version 23.0 (SPSS, IBM). The variables were summarized using frequencies, proportions, means and standard deviation. Chi Square was used for test of significance with the p-value set at P < 0.05. Results: Of the 261 participants 176 (67.5 % percent) were aged 25-34 years; majority (244,93.5 %) had tertiary education while (189, 72.4 %) were skilled workers or professionals. Most of the women (243, 93.2 %) were Para 1-3 and the pregnancy was planned (80.8 %) while financing was mostly out of pocket (60.9 %). Only one-third of the participants has at least eight (8) antenatal contacts. In overall rating, most women (90.0 %) were satisfied with the antenatal care services received. The highest rating of satisfaction was with the competence of the service providers (90.4 %) especially with the care given to them and their unborn babies (90.4 %). The parity, distance of their home from antenatal clinic, number of antenatal contacts, number of health education sessions attended, total time spent, attitude of health workers, cost of services and desire to register again at the facility were statistically associated with patient's satisfaction. Also, the number of antenatal visits was statistically associated with the fetal outcome. Conclusion: There is a high overall level of satisfaction with antenatal services among postpartum women in UCH. It is important to encourage women to register early to ensure they have adequate number of antenatal contacts and also participate in the health education sessions.